Evaluation of carrageenan gel properties at different concentrations of calcium chloride dihydrate salt - Nur Anis Alisya, Kamarol Zani; Fatmawati, Adam; Nurul Aini, Mohd Azman; Nor Hanuni, Ramli (Universiti Kebangsaan Malaysia, 2023)
Aromatherapy is an alternative therapy for Complementary and Alternative Medicine (CAM) to relieve mild depression in individuals. This study aimed to evaluate the effect of incorporating calcium chloride dihydrate in carrageenan gel to increase stability property. The gel formulation was produced from a mixture of semi-refined carrageenan, sodium benzoate, alginic acid, polyethene glycol (PEG) and sorbitan monolaurate (Span 20) followed by the inclusion of calcium chloride dehydrate (CCD) at 0%, 0.5%, 1%, 1.5%, and 2% concentrations. The effects of CCD concentration on rheology, gel Bloom strength, morphology, and thermal properties were investigated. The viscosity and shear stress decreased on incorporating of CCD in the carrageenan gel formulation. The highest viscosity of the control gel was 597.84 mPa.s. The intersection of G' and G" at various concentrations of CCD salts in the gel formulation demonstrated that the increment of salt concentration resulted in a faster gelation process in the range 56.6 to 50.43 °C. The gel Bloom strength increased from 830.04 g at 0.5% CCF salt to 1331.39 g at 2% CCD. The highest gel strength of 1324.59 g was achieved with 2% CCD and a melting temperature of 194.4 °C. The weight loss rate for the control gel was 28.88%, the lowest weight loss rate for 2% CCD gel was 11.82%. The residual gel weight was also highest for 2% CCD: 16.74% after 21 days. A high residual gel weight reflects the stability of the carrageenan gel formulation to retain the product and last as aromatherapy gel product. The morphology images showed a highly porous gel structure on addition of CCD salts. In conclusion, CCD salt is capable of forming a strong interaction with the gel matrix to produce a stable gel.